Well Test and Short Term Multiple Rate Flow Tests Analyses to Successfully Hydraulic Fracturing Program of Block X - Muhammad Dimas Adiguna; Muhammad Taufiq Fathaddin; Hari Karyadi Oetomo (Journal of Earth Energy Science, Engineering, and Technology, 2018)
Well test analysis was conducted to determine the characteristics of reservoir rocks. From the well test analysis it is obtained information such as permeability and skin factor. The skin factor is a quantity indicating the presence of disturbance in the formation as a result of drilling operations, production operations, perforating casing, gravel pack installation, remedial well work, acidizing operation, and hydraulic fracture operation. The objective of this research is to determine the relationship of multi rate test method of Jones, Blount, and Glaze and the comparison result among pressure buildup test and pressure drawdown test analyses, using Kappa software or manually calculation. Therefore, in this paper will study the method of Jones, Blount, and Glaze and the well test analyses to determine further work of the wells on block X. The data used in this paper is secondary data, namely the results of well test from three wells.Applying drawdown test analysis of A, Y, and Z wells yield skin factor values of 3.37; 27.10; and -1.39. Where in buildup pressure Horner method analysis of A, Y, and Z wells yield skin factor values of 16.10; 11.18; and -2.07. In the method of type curve derivatives the drawdown analysis of A, Y, and Z wells yield skin factor values of 7.04; 11.18; and 4.20. The analysis of pressure buildup, of A, Y, and Z wells yield skin factor value of 25.11; 14.47; and 1.93. In the analysis using Kappa software of A, Y, and Z wells yield skin factor values of 5.56; 10.2; and 2.00. The skin results of these wells indicate the formation damages. The Short Term Multiple Rate Flow Tests analysis using Jones, Blount, and Glaze method from the plots of Δp/q versus oil flow rate (q) are b’ high and b’/b low. These indicate that the three wells are encountering formation damages. The Jones, Blount, and Glaze method as well as the pressure buildup and pressure drawdown test analyses in block X indicate that these wells require to be stimulated.